Three-dimensional hierarchical semi-polar GaN/InGaN MQW coaxial nanowires on a patterned Si nanowire template. Issue 4 (23rd March 2020) - Johar, Muhammad Ali; Kim, Taeyun; Song, Hyun-Gyu; Waseem, Aadil; Kang, Jin-Ho; Hassan, Mostafa Afifi; Bagal, Indrajit V.; Cho, Yong-Hoon; Ryu, Sang-Wan
Abstract : We have demonstrated for the first time the hybrid development of next-generation 3-D hierarchical GaN/InGaN multiple-quantum-well nanowires on a patterned Si nanowire-template and their optical characterizations are also conducted. Abstract : We have demonstrated for the first time the hybrid development of next-generation 3-D hierarchical GaN/InGaN multiple-quantum-well nanowires on a patterned Si nanowire-template. The patterned Si nanowire-template is fabricated using metal-assisted chemical-etching, and the conformal growth of the GaN/InGaN multiple-quantum-well (MQW) coaxial nanowires is conducted using metal–organic-chemical-vapor-deposition by the two-step growth approach of vapor–liquid–solid for the GaN core and vapor–solid for the GaN/InGaN MQW shells. The growth directions of the GaN nanowires are confirmed by transmission electron microscopy and selected area electron diffraction patterns. The emission of the GaN/InGaN MQW nanowire is tuned from 440 nm to 505 nm by increasing the InGaN quantum-well thickness. The carrier dynamics were evaluated by performing temperature-dependent time-resolved photoluminescence measurement, and the radiative lifetime of photogenerated electron–hole pairs was found to range from 30 to 35 ps. A very high IQE of 56% was measured due to the suppressed quantum-confined Stark effect which was enabled by the semi-polar growth facet of the GaN/InGaN MQWs. The demonstration of the growth of the hybrid 3-D hierarchical GaN/InGaN MQW nanowires provides a seamless platform for a broad range of multifunctional optical and electronic applications.